1995
DOI: 10.1007/bf00214186
|View full text |Cite
|
Sign up to set email alerts
|

Maternal origin of nucleated erythrocytes in peripheral venous blood of pregnant women

Abstract: We studied the origin of nucleated red blood cells (NRBC) in peripheral venous blood samples from 40 pregnant women carrying a male fetus, using a technique that allows direct chromosomal analysis by in situ hybridisation on immunologically and morphologically classified cells. Samples from ten nulligravid women were studied as controls. NRBC were enriched by negative magnetic activated cell sorting (miniMACS) using anti-CD45 monoclonal antibody. NRBC were detected by alkaline phosphatase anti-alkaline phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
2
7

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 15 publications
4
52
2
7
Order By: Relevance
“…Combining these results, we could conclude that these three cells were of maternal origin. This finding also gives evidence that NRBCs in maternal blood are of both fetal and maternal origin, and it is comparable to those of previous studies (Ganshirt et al 1994;Slunga-Tallberg et al 1995von Eggeling et al 1997;Holzgreve et al 1998;Troeger et al 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Combining these results, we could conclude that these three cells were of maternal origin. This finding also gives evidence that NRBCs in maternal blood are of both fetal and maternal origin, and it is comparable to those of previous studies (Ganshirt et al 1994;Slunga-Tallberg et al 1995von Eggeling et al 1997;Holzgreve et al 1998;Troeger et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…The problem is that NRBCs in maternal peripheral blood are of both fetal and maternal origin (Ganshirt et al 1994;Slunga-Tallberg et al 1995von Eggeling et al 1997;Holzgreve et al 1998;Troeger et al 1999). However, despite the fact that nucleated erythrocytes in maternal peripheral blood are of fetal and maternal origin, many researchers have claimed that they can diagnose various disorders using NRBCs in maternal peripheral blood, such as hemoglobinopathies (Di Naro et al 2000), Rhesus type, and Duchenne muscular dystrophy (Sekizawa et al 1996a,b).…”
mentioning
confidence: 99%
“…While use of Abs against HBF Á-chain has improved recognition of NRBCs, it is not a 100% specific marker for fetal cells, since it is known that women during pregnancy may produce and release in the circulation adult Hb F Á-positive NRBCs [2][3][4]. In our study we identified 5 cases in which the fetus was shown correctly by FISH to be male, but NRBCs with two X signals were also detected in the CVS supernatant [1].…”
Section: Introductionmentioning
confidence: 72%
“…Analysis of this haemoglobin chain revealed it was most probably maternal in origin. Also Oosterwijk et al (1998b) and Slunga-Tallberg et al (1995) found that a considerable proportion of HbF-positive NRBCs in the blood of pregnant women is maternal.…”
Section: Discussionmentioning
confidence: 99%